Extracellular thiamine concentration influences thermogenic competency of differentiating neck area-derived human adipocytes - Vinnai, Boglárka Ágnes; Arianti, Rini; Győry, Ferenc; Bacso, Zsolt; Fésüs, László; Kristóf, Endre (Frontiers in Nutrition, 2023)
Brown adipose tissue (BAT) dissipates energy in the form of heat majorly via the mitochondrial uncoupling protein 1 (UCP1). The activation of BAT, which is enriched in the neck area and contains brown and beige adipocytes in humans, was considered as a potential therapeutic target to treat obesity. Therefore, finding novel agents that can stimulate the differentiation and recruitment of brown or beige thermogenic adipocytes are important subjects for investigation. The current study investigated how the availability of extracellular thiamine (vitamin B1), an essential cofactor of mitochondrial enzyme complexes that catalyze key steps in the catabolism of nutrients, affects the expression of thermogenic marker genes and proteins and subsequent functional parameters during ex vivo adipocyte differentiation. Therefore, we differentiated primary human adipogenic progenitors that were cultivated from subcutaneous (SC) or deep neck (DN) adipose tissues in the presence of gradually increasing thiamine concentrations during their 14 day long differentiation program. Higher thiamine levels resulted in increased expression of thiamine transporter 1 and 2 both at mRNA and protein levels in human neck area-derived adipocytes. Gradually increasing concentrations of thiamine led to increased basal, cAMP-stimulated, and proton-leak respiration along with elevated mitochondrial biogenesis of the differentiated adipocytes. The extracellular thiamine availability during adipogenesis determined the expression levels of UCP1, PGC1a, CKMT2, and other browning-related genes and proteins in primary SC and DN-derived adipocytes in a concentration-dependent manner. Providing abundant amounts of thiamine further increased the thermogenic competency of the adipocytes. Our study raises the possibility of a novel strategy with long-term thiamine supplementation, which can enhance the thermogenic competency of differentiating neck area-derived adipocytes for preventing or combating obesity.